Diverse Family Types and Out-Of-School Learning Time of Young School Age Children - Ono, Hiromi (2010)
=Sources of differentials in out-of-school learning time between children in first marriage biological parent families and children in six nontraditional family types are identified. Analyses of time diaries reveal that children in four of the six nontraditional family types spend fewer minutes learning than do children in first marriage biological parent families. In all four cases, however, the differentials are explained by the presence of siblings age 18+, lower levels of family income, or younger maternal age.